DNA fingerprinting of medicinal rice ’Njavara’ using microsatellite markers: Microsatellite DNA fingerprinting: Njavara - A ROBERT, SHIJO; Devaki, Girija; P S, Abida; A G, Kiran; Francies, Rose Mary; Muhammed Ameer; S, Pandiaraj (ORYZA-An International Journal of Rice, 2025)
Njavara is a unique medicinal rice cultivated in Kerala. This study presents a detailed investigation into the DNA fingerprinting of Njavara rice using Simple Sequence Repeat (SSR) markers. Using 19 selected SSR markers, fingerprinting was conducted on three Njavara accessions (Black Njavara - TGC366, White Njavara - TGC389, and Karanjavara - TGC90), Rakthasali (traditional medicinal rice), and Vaishak (KAU variety). A comprehensive fingerprint, combining all samples and markers, was created. A set of 10 markers producing unique amplicons in the three Njavara accessions were validated using 10 selected KAU varieties. Four markers (RM340, RM493, RM434, and RM202) were effective in distinguishing Njavara from KAU varieties. The dendrogram highlighted two clusters, clearly separating Njavara from non-Njavara types. These markers prove valuable in accurately discerning Njavara rice and provide insights into its genetic diversity.